Bilateral diffuse lamellar keratitis following bilateral simultaneous versus sequential laser in situ keratomileusis. Issue 9 (20th August 2003) - McLeod, S D; Tham, V M-B; Phan, S T; Hwang, D G; Rizen, M; Abbott, R L
Abstract : Aim: To determine the difference in the incidence of bilateral diffuse lamellar keratitis (DLK) in patients undergoing simultaneous versus sequential laser in situ keratomileusis (LASIK) as an indication of intrinsic risk for inflammation. Methods: A retrospective non-comparative case series of 1632 eyes that had undergone bilateral, simultaneous or sequential LASIK between April 1998 and February 2001 at a university based refractive centre by three surgeons. All cases that developed clinically evident DLK were identified and reviewed. In order to identify isolated cases and exclude those caused by environmental factors, when more than one patient in a given session developed DLK, the session was excluded. The main outcome measure was the incidence of unilateral and bilateral isolated, non-epidemic DLK. Results: Of 1632 eyes, 126 eyes (7.7%) of 107 patients developed at least grade 1 DLK. In six operating sessions, DLK was observed in more than one patient per session, and on this basis 13 patients were excluded. 16 of the 94 remaining patients developed DLK in both eyes (17.0%). Six of 41 patients (14.6%) in the simultaneous group, versus 10 of 53 patients (18.9%) in the sequential group developed bilateral DLK (p >0.5). Conclusion: In isolated, non-epidemic bilateral DLK, a similar incidence was observed regardless of whether the surgery was simultaneous or sequential, suggesting an underlying intrinsic cause for DLK.